Giving in Unilaterally Risky Dictator Games: A Model of Allocation Decisions Under Existential Threat - Sarah Franziska Kovatsch (Junior Management Science (JUMS), 2020)
This study reports experimental results from variations of the standard dictator game that capture different variants of unilaterally risky allocation decisions where only the dictator's payoff is subject to risk. Thereby, it addresses the question of whether decisions under existential threat, modeled as a risk to the dictator's payoff, encourage or discourage generosity in individual decision making. It aims at bridging the gap between experimental economics and psychological research on the behavioral impact of mortality salience. Results show that giving in unilterally risky dictator games increases with the risk imposed on the dictator's payoff. Risk aversion falls short of explaining the increase in generosity. Instead, the observed behavior is most likely motivated by a preference for efficient capital employment. Moreover, dictator games prove to be an apt model for decisions under existential threat.
Keywords: 650; dictator games; risky decisions; mortality salience; generosity; existential threat